EFFECT OF ELECTROLYTIC CELL OPERATING PARAMETERS ON SODIUM HYPOCHLORITE FORMATION AND ENERGY CONSUMPTION - COLLANA, JUAN TAUMATURGO MEDINA (2024)
SODIUM HYPOCHLORITE (NACLO) IS USED ON A LARGE SCALE FOR WATER DISINFECTION, FABRIC BLEACHING, AND ODOR REMOVAL. IT IS PREFERRED DUE TO THE ENVIRONMENTAL RISK OF LIQUID CHLORINE ASSOCIATED WITH STORAGE AND TRANSPORT. THE OBJECTIVE OF THE RESEARCH WAS THE ELECTROCHEMICAL GENERATION OF SODIUM HYPOCHLORITE FROM AN AQUEOUS SOLUTION OF SODIUM CHLORIDE. DIFFERENT OPERATING CONDITIONS AFFECTING THE SODIUM HYPOCHLORITE GENERATION PROCESS WERE STUDIED, INCLUDING ELECTRICAL POTENTIAL (6 AND 10 V), SODIUM CHLORIDE CONCENTRATION (80 AND 120 G/L), AND ELECTROLYSIS TIME (30 AND 60 MINUTES. TO ANALYZE THE EFFECT OF THE FACTORS WITH RESPECT TO THE RESPONSE VARIABLE SUCH AS SODIUM HYPOCHLORITE CONCENTRATION AND ENERGY CONSUMPTION PER KILOGRAM OF HYPOCHLORITE PRODUCED, A TWO-LEVEL FACTORIAL DESIGN WAS USED FOR EACH FACTOR. THE BEST OPERATING CONDITIONS PRODUCED WHEN THE APPLIED ELECTRIC POTENTIAL WAS 10 V, SODIUM CHLORIDE CONCENTRATION 120 G/L, AND TREATMENT TIME OF 60 MINUTES REACHING A CONCENTRATION OF 2276 G/L NACLO AND A FREE CHLORINE PERCENTAGE OF 0.23 %. AS WELL, THE ENERGY CONSUMPTION PER KILOGRAM OF HYPOCHLORITE IS IN THE RANGE OF 3.31 AND 11.78 KWH/KG. © 2024 BY CEE (CENTER OF EXCELLENCE IN ELECTROCHEMISTRY).